The challenges of implementing Machinoeki Concept in Taiping Town / Yong Adilah Shamsul Harumain ... [et al.] - Shamsul Harumain, Yong Adilah; Nordin, Nikmatul Adha; Azmi, Nur Farhana; Morimoto, Akinori; Teppei, Osada; Murad, Mirahida (2018)
Machinoeki is a unique community involvement concept, empower with hospitality and volunteerism that benefits the town revival. The core principal in Machinoeki concept is to inspirecommunity through the idea of space sharing at their building premises where visitor can rest, get some information about the town, and also used the toilet service for free. The use of existing resources within the building indicates that the concept does carry the spirit of community participationas a non-direct social service from the local community to the town development. This is an interesting concept as community works voluntarily to help the local government to revitalize the town, nurture the idea of hospitality, which means cultivate and educate good services. This concept is not a medium to get local government to wash their hands but to get the community work bottom up and work hand in hand with the local government to rebuild and revive the town. Nonetheless, the implementation of this concept faced a lot of challenges from the building owners involved and received mix responses among the local community. Are Malaysians ready to embrace such concept and how do they react to his concept? This paperexplain about the challenges faced by the researcher to introduce this concept to the building owners and local community in Taiping town for the past year.